(untitled) (Research, Society and Development, 2020)
Research on the chemical composition and pharmacological activities of geopropolis produced by stingless bees (Hymenoptera, Apidae, Meliponini) may contribute to expand its use of propolis-based formulations in the clinical context. Thus he study aimed to evaluate the chemical composition and biological activity of the hydroethanolic extract (HEG) of the geopropolis of Partamona cupira, obtained in the semiarid region of northeast Brazil. Chemical analyses of HEG were carried out using HPLC-DADESI-MS/MS. The antioxidant activity of extracts was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay method and cytotoxic activity by the in vitro MTT method [brometo de 3- (4.5dimetiltiazol-2-il)-2.5-difeniltetrazolio]. The antibacterial activity of the HEG was evaluated through the disc-diffusion test on agar and measurement of the promoted by the extract in different concentrations. The genoprotective potential of the HEG was evaluated through the comet assay on fibroblasts of L929, co-treated with the extract and submitted to genotoxicity induction with H2O2. We also investigated the healing effect of the cream containing geopropolis (10%) on experimental skin wounds in Wistar rats. The HEG presented in its composition phenolic compounds of high biological activity, as well as revealed high antioxidant activity and promoted genoprotective effect by reducing DNA damage from L929 fibroblasts. The HEG presented antimicrobial activity promoting inhibition of S. aureus, S. pyogenes, E. coli and E. aerogenes. The topical use of the cream containing geopropolis promoted wound closure and faster reepithelialization in relation to the control group, in addition to a less intense inflammatory reaction, increased fibroblastic proliferation and collagen deposition.